Influence of Product Quality, Price, Brand Image and Promotion on Customer Satisfaction on Lazada (Case Study in Pekanbaru City Communities) - Panjaitan, Harry Patuan; Vinson, Vinson; Yani, Fitri; Sitompul, Silvia Sari; Sari, Olivia; Lubis, Wahyu May Chrisfin (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This study aims to determine and analyze the effect of product quality, price, brand image and promotion on customer satisfaction at Lazada (Case Study of Communities in Pekanbaru City). Determination of the sample in this study using accidental sampling. This study uses primary data. In this study, primary data were obtained directly from respondents by dividing questionnaires or lists of statements on a predetermined sample. Secondary data is generally in the form of evidence, historical records or reports arranged in published archives. The method used is multiple linear regression analysis with a sample of 150 respondents. The research results show that product quality, price, and promotion have a significant effect on customer satisfaction at Lazada, while brand image has no significant effect on customer satisfaction at Lazada.